Pengembangan Website Direktorat Jenderal Industri Agro Kementerian Perindustrian - Sadif, M R; Wibawa, J C (Program Studi Sistem Informasi, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia., 2021)
The Directorate General of Agro-Industry is one of the implementing elements of the duties of the Minister of Industry, which has the task of organizing the formulation and implementation of policies. In order to encourage the growth and development of the role of the agro-industry, especially in providing informative information, which is very important in the current era of technology 4.0, publications and information facilities are needed regarding the development of the agro-industry. The design of this study used a descriptive method, using an object-oriented approach, while its development used a prototype model. This study aims to develop a website that is in accordance with several important factors that need to be considered so that website development can touch the quality side of the Ministry of Industry, Directorate General of Agro-industry which is in line with Law Number 14 of 2008 concerning Information Disclosure. This research produces a quality website at the Ministry of Industry, Directorate General of Agro-Industry, and meets the principles of good governance in accordance with Presidential Instruction No. 3 of 2003. So that the transparency and accountability of the information on this website are expected to have an impact on increasing the confidence of both local and foreign investors.